Hemostasis in Intracranial Hemorrhage - Gulati, Deepak; Dua, Dharti; Torbey, Michel T. (Frontiers in Neurology, 2017)
Spontaneous non-traumatic intracerebral hemorrhage (ICH) is associated with high morbidity and mortality throughout the world with no proven effective treatment. Majority of hematoma expansion occur within 4 h after symptom onset and is associated with early deterioration and poor clinical outcome. There is a vital role of ultra-early hemostatic therapy in ICH to limit hematoma expansion. Patients at risk for hematoma expansion are with underlying hemostatic abnormalities. Treatment strategy should include appropriate intervention based on the history of use of antithrombotic use or an underlying coagulopathy in patients with ICH. For antiplatelet-associated ICH, recommendation is to discontinue antiplatelet agent and transfuse platelets to those who will undergo neurosurgical procedure with moderate quality of evidence. For vitamin K antagonist-associated ICH, administration of 3-factor or 4-factor prothrombin complex concentrates (PCCs) rather than fresh frozen plasma to patients with INR >1.4 is strongly recommended. For patients with novel oral anticoagulant-associated ICH, administering activated charcoal to those who present within 2 h of ingestion is recommended. Idarucizumab, a humanized monoclonal antibody fragment against dabigatran (direct thrombin inhibitor) is approved by FDA for emergency situations. Administer activated PCC (50 U/kg) or 4-factor PCC (50 U/kg) to patients with ICH associated with direct thrombin inhibitors (DTI) if idarucizumab is not available or if the hemorrhage is associated with a DTI other than dabigatran. For factor Xa inhibitor-associated ICH, administration of 4-factor PCC or aPCC is preferred over recombinant FVIIa because of the lower risk of adverse thrombotic events.